(untitled) (Culturas Científicas, 2024)
This work addresses the ideal of science free of extra epistemic values. In this regard, the discussion is situated within the framework of authors who subscribe to the so-called scientific pluralism, who, in general, have a position more inclined to accept the influence of extra-epistemic values in the sciences, such as moral, political and social values. In particular, the positions of Helen Lóngino, Heather Douglas and John Dupré are reviewed, analyzing whether or not the criticisms developed mainly by Hugh Lacey are applicable, who, being a pluralist, continues to support the ideal of value-free science. It is concluded that there are good arguments that support the influence of extra epistemic values in the sciences; However, its extension may be subject to debate or nuanced. In this regard, a position is taken based on the position of John Dupré, which recognizes that in certain areas of science- such as particle physics- there is no extra epistemic burden. Likewise, it is concluded that, although the ideal of a completely value-free science must be rejected, its dimension as a regulative ideal may have some relevance, imposing a greater challenge for positions that seek to refute the ideal in question.